To solve this expression, we can start by multiplying and dividing from left to right, following the order of operations.
First, we can multiply:
(-3) ÷ (34) × (27) × (-516) ÷ (57) = (-3/34) × (27) × (-516) ÷ (57)
Next, we can divide:
(-3/34) × (27) × (-516) ÷ (57) = (-3/34) × (27) × (-516/57)
Now, let's simplify each part:
(-3/34) × (27) × (-516/57) = (-3 × 27 × -516) / (34 × 57)
(-3 × 27 × -516) = 41,868
(34 × 57) = 1938
Finally, we can divide:
41,868 / 1938 = 21.6
Therefore, (-3) ÷ (34) × (27) × (-516) ÷ (57) equals 21.6.
Use the properties of operations and rules for multiplying and dividing to solve: (−3)÷(34)×(27)×(−516)÷(57)
1 answer